Perception of successful aging in faculty of a school of medicine - Martina, Martha (2019)
Introduction. In our country changes are taking place in the structure by age in the last decades, one of the most important is the increase of the older adult population. Objectives. To determine the perception of living a successful aging and identify some variables associated with this perception in the elderly teachers of the Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Methods. Cross-sectional and correlational study. Sample of 106 older adult teachers selected for convenience, from september to november 2017. The Successful Aging Inventory of Meredith Troutman was used by the author. Results. The mean age was 67,38 ± 5,77 with a range between 60 to 87 years. 67% were married; 47,7% lived with their partner and relatives, only four teachers (3,8%) lived alone without any support. 70,1% (74) work in the university for 26 years or more; 46,7% (50) are associates; 64,2% (68) work as part time; 46,7% (49) have a master’s degree and 26,4% (28) belong to the ONP Law 20530. 76,3% of the elderly teachers declared that they perceive a successful aging. The dimensions that contribute most to successful aging were functional mechanisms of performance (88,7%) followed by satisfaction with life (71,7%) and intrapsychic factors (69,5%). Conclusions. Successful aging is a majority in the elderly teachers of the faculty of medicine, probably as a result of a process of adaptation to the changes of aging and to an intense intellectual prior activity to this stage.